2021
DOI: 10.3906/sag-2008-285
|View full text |Cite
|
Sign up to set email alerts
|

Could serum albumin value and thrombocyte/lymphocyte ratio be an important prognostic factor in determining the severity of COVID 19?

Abstract: Background and aim: Creating potential clinical markers for risk assessment in patients with COVID-19 continues to be an area of interest. In this study, we aimed to evaluate whether serum albumin level and thrombocyte/lymphocyte ratio are related to the severity of the disease. Materials and methods:The patients were divided into two groups according to the severity of disease. Demographic data, serum albumin value, lymphocyte count, TLO-1 values (thrombocyte/lymphocyte ratio-1), the highest thrombocyte count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…It also has to be considered that these initial studies were made in Chinese populations, with an evident limitation considering the potential generalization of the findings. Similar results were obtained in posterior specific studies not only in Chinese [ 17 , 18 ] but also in Caucasian populations [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The main limitation of these studies was the usual small sample size, as shown in recent meta-analysis, that confirmed the utility of SA as a prognostic marker in hospitalized acute COVID-19, although again indicating a very high heterogeneity of the analyzed literature, as well as small samples [ 26 , 27 ].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…It also has to be considered that these initial studies were made in Chinese populations, with an evident limitation considering the potential generalization of the findings. Similar results were obtained in posterior specific studies not only in Chinese [ 17 , 18 ] but also in Caucasian populations [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The main limitation of these studies was the usual small sample size, as shown in recent meta-analysis, that confirmed the utility of SA as a prognostic marker in hospitalized acute COVID-19, although again indicating a very high heterogeneity of the analyzed literature, as well as small samples [ 26 , 27 ].…”
Section: Introductionsupporting
confidence: 88%
“…As a consequence, low levels of albumin indicate a weakened general status and diminished host immune response, which is a well-known factor associated with comorbidity [ 12 ]. In accordance with this observation, an increasing number of studies that have specifically examined the potential predictive capacity of SA in COVID-19 have shown this parameter to be a good course indicator in terms of clinical deterioration, need for admission to the ICU, and mortality in patients with low SA values [ 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 79%
“…As in COVID-19, in increased inflammation and OS-related pathophysiological processes, albumin is irreversibly oxidized [ 38 , 39 ]. It has been suggested in many studies that, hypoalbuminemia detected on admission could be predictive of the negative outcomes of COVID-19 [ 40 , 41 ]. Ducastel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, SA predicts ICU admission with a HR score of 1.87, 95% CI 1.05-3.32, p = 0.034 18 . A study conducted in 63 COVID-19 patients from Turkey revealed that SA at admission predicts ICU admission with a cutoff point of ≤ 36 g/L, AUC of 0.989 (95% CI 0.924-1.00; p < 0.001), sensitivity of 96.7%, and specificity of 93.9% 19 . On the other hand, a study of 128 COVID-19 patients from Dubai showed that SA failed to predict ICU admission (AUC 0.256, 95% CI 0.146-0.366) 20 .…”
Section: Serum Albuminmentioning
confidence: 99%
“…Since the coronavirus disease 2019 (COVID- 19) outbreak began in December 2019, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has quickly spread worldwide 1 . COVID-19 presentation is heterogeneous and ranges from asymptomatic disease to severe illness characterized by pneumonia, acute respiratory distress syndrome (ARDS), and sepsis that may eventually lead to death 2 .…”
Section: Introductionmentioning
confidence: 99%